This thing of darkness : Eisenstein's Ivan the Terrible in Stalin's Russia - Neuberger, Joan, 1953- (Cornell University Press, 2019)
"Eisenstein's diaries and production notebooks show that he carefully planned Ivan the Terrible to be a devastating critique of Stalinism, a profound study of the tragedy of absolute power, and a wildly innovative use of montage, all wrapped inside a narrative that would receive Stalin's approval"--